Game worker solidarity: Mapping collective actions in the video games industry - Kelmore, Austin; Woodcock, Jamie (Eludamos: Journal for Computer Game Culture, 2023)
This commentary discusses the Game Worker Solidarity (GWS) Project. It documents instances of collective action in the games industry, presenting the data in a map and accompanying database. The aim of the project is to facilitate sharing information on the emergent movement for unionisation in the games industry after 2018, as well as archiving the longer history of worker resistance. We argue that understanding worker organisation—both the existing forms of collective action as well as the potential in the future—is vital for understanding the future of games and game production.